2023
DOI: 10.3389/fnut.2023.1259053
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the temporal trend and daily profiles of the dietary purine intake among Chinese residents during 2014 to 2021

Shiwen Li,
Xin Liu,
Xiwu Jia
et al.

Abstract: The incidence of hyperuricemia is on the rise in China, primarily due to dietary habits. However, limited data exists regarding dietary purine intake in the country. This study aimed to estimate the daily dietary purine intake among Chinese residents from 2014 to 2021 and evaluate the temporal trend using joinpoint regression analysis. The analysis revealed an annual percentage change (APC) of 0.8% (95% CI: 0.1–1.5%) in dietary purine intake prior to the joinpoint (2014–2019). Following the joinpoint (2019–202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Its prevalence can be affected by excessive intake of high purine and high fructose foods [6,14]. Previous research has shown that hyperuricemia is more prevalent in coastal areas due to excessive purine intake [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Its prevalence can be affected by excessive intake of high purine and high fructose foods [6,14]. Previous research has shown that hyperuricemia is more prevalent in coastal areas due to excessive purine intake [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…After 6 weeks’ successful modeling, the NC and SLM groups were treated with normal chow diet, and the treatment groups were orally administered with normal chow diet (the analysis of the nutritional content of the daily diet is shown in the supporting information, Table S3) with low‐(LMTD, 83.3 mg kg −1 bw day −1 ) and with high‐dose sacha inchi albumin (HMTD, 166.7 mg kg −1 bw day −1 ). The high‐dosage of SIA was determined based on the daily maximum protein intake (55 g d −1 ) for human adults (60 kg) adjusted according to the actual average weight for the mice and was calculated as 55 × 9.01/60 × 0.02018 = 166.7 mg kg −1 bw day −1 , 28,29 the low‐dose group was half the high‐dose one, according to the previous report 30 . They were allowed access to water and food ad libitum for 6 weeks during which the bodyweight and food intake were recorded daily for each rat.…”
Section: Methodsmentioning
confidence: 99%